ANALISIS PENDAPATAN USAHA BUDIDAYA CACING SUTERA DENGAN MEDIA NAMPAN BERTINGKAT ; KASUS USAHA KELUARGA DI DESA KARANGTEJO KEDU TEMANGGUNG JAWA TENGAH DAN UJI COBA DI BELITANG OKU TIMUR - Muridin (Jurnal Bakti Agribisnis, 2018)
This research aims to know the techniques of cultivation and silk worm life terms with the media tray multilevel. To calculate the income level of the silk worm cultivation efforts with media in the village-floor tray Karangtejo Kedu Temanggung Central Java as well as key factors for the development of silk worm in Belitang OKU East. Data processing methods used are of financial analysis (cost of production, production, reception, income and RC ratio) and non financial analysis (Bahaninput, Agroklimat, potential market). The research results obtained with silk worm cultivation media tray multilevel can be dikebangkan in the East viewed from the OKU Belitang market potential is great with silk worms requests in one month about 2815 glasses. The available input materials among others, silk worm seed dregs of tofu, chicken manure, fine bran. Temperature suitability trials with cultivation in Eastern silk worm Belitang OKU can adapt and expand the container trays. Production costs incurred in one fell prosesproduksi amounting to Rp 9,256,350, Rp gained acceptance 18,977,000 and revenue amounting to Rp 9,720,650 with a value of RC ratio of 2.05.